Knowledge and Attitude of Nurses towards Hepatitis B and C Prevention and Transmission - Sumera Jabeen, Mansoor Ghani, Samina Kausar, Rahila Mushtaq, Asma Khalid, Misbah Hanif, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Nurses are considered a key member of health care delivery system who are providing essential care to their clients. Aim: To assess knowledge and attitude of charge nurses, working in tertiary care hospitals of Lahore. Study Design: Cross-sectional descriptive study. Methodology: A sample size of 272 staff nurses working in four tertiary care hospitals of Lahore were enrolled by using method of non-probability convenient sampling. Data was collected by adopted questionnaire. Data was analyzed by SPSS software, version 23. Results were compiled and presented as frequencies and percentages. Frequencies were computed for categorical variables. Chi-square / Fisher’s exact test was used to determine the association of knowledge and attitude. A p-value ≤ 0.05 was taken as significant. Results: The result revealed that 36.4% nurses had good level of knowledge and 9.6% nurses had excellent knowledge related to Hepatitis B and C prevention and transmission. Majority of the participants 76.5% depicted positive attitude. Practical Implication: Nurses are the primary source of information for the public, so it's critical to assess their knowledge and attitudes about these disorders. A better understanding of health workers' knowledge and attitudes about the risk of liver disease, particularly among nurses, will aid in the creation of suitable preventative initiatives for this demographic. This study helped in Program planning for monitoring and improving the nursing care services at health care setups. Conclusion: We concluded that beside a sub optimal level of knowledge of viral Hepatitis B and C, nurses have been willingly providing care to their clients with positive attitude. Keywords: Patient Satisfaction, Nursing Care, Prevention and Knowledge.